Overview of the Development of International Trade Community Welfare in Mataram City (review of poverty levels 2020-2024) - Indah, Tiska Asri; Agustiani, Eka (West Science Journal Economic and Entrepreneurship, 2025)
This study analyzes the relationship between international trade and societal welfare in the Province of Nusa Tenggara Barat (NTB), focusing on poverty levels during the period 2020–2024. Utilizing secondary data from the Central Bureau of Statistics (BPS) and a descriptive quantitative approach, the research describes the trends in exports, imports, and poverty rates, and evaluates their descriptive interrelations. The results indicate that although exports increased significantly—mainly driven by mining commodities—the decline in poverty was largely driven by post-pandemic recovery in local labor-intensive sectors rather than merely increased exports. Therefore, international trade contributes to NTB’s economic growth, but its impact on poverty reduction is limited and indirect. The study recommends economic diversification, strengthening labor-intensive sectors, and empowering the poor to ensure a more equitable distribution of trade benefits.